ChemInform Abstract: Chemical Tools for Interrogating Inositol Pyrophosphate Structure and Function. Issue 51 (5th December 2016) - Brown, Nathaniel W. Jr.; Marmelstein, Alan M.; Fiedler, Dorothea
Abstract: Review: 117 refs.